IMPACT OF ACID WASHING AND CHELATION ON Mg(OH)2-BASED HYDROGEN PEROXIDE BLEACHING OF MIXED HARDWOODS CMP AT A HIGH CONSISTENCY - Somayeh Ghasemi (BioResources, 2010)
The removal of transition metal ions is crucial for improving the efficiency of subsequent peroxide bleaching. Acid-washing and chelation have been proposed for such a purpose. However, their influences on the Mg(OH)2-based peroxide bleaching of hardwood pulps at a high consistency have not been well documented in the literature. In this work, we studied the influence of acid-washing using sulfuric acid or chelation using diethylenetriaminepentaacetic (DTPA) on the Mg(OH)2- or NaOH-based hydrogen peroxide bleaching efficiency, effluent properties of bleaching filtrates, and paper properties. The results showed that for Mg(OH)2-based peroxide bleaching, the pulp yield and water retention value of acid-washed pulp were higher than those of the chelated pulp; the chemical oxygen demand (COD) and turbidity of the bleaching filtrates for the acid-washed pulp were lower than those of the chelated pulp. The bleached acid-washed pulp had lower strength properties than bleached chelated pulp did. Additionally, at a high pulp consistency (25%), the Mg(OH)2-based process had a higher bleaching efficiency and superior bleaching effluent properties, but a lower strength properties, in comparison with the NaOH-based process.